1999
DOI: 10.1111/j.1754-4505.1999.tb01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with Autistic Disorder (AD) presenting for dental treatment: a survey and chart review

Abstract: A group of 43 patients with AD (mean age, 13.5; SD, 5.9 yrs) was identified from the University Hospital School Pediatric Dentistry Clinic. We reviewed the patients' charts to obtain demographic data, dental findings, and the management techniques used for treatment. The patients were divided into groups according to Frankl's categories of behavior, ranging from definitely negative to positive. Descriptive data are provided for each group. Commonly used communications and pharmacological management techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 0 publications
11
79
1
Order By: Relevance
“…In the pre-test, 73.7 % of children and 67.6 % of adults showed a reluctant behavior (Frankl values 1 and 2); a similar percentage to that observed initially by Lowe and Jędrychowski (1987), Klein and Nowak (1999), Chaushu and Becker (2000), Marshall et al (2008), and Subramaniam and Gupta (2011) with 70, 72, 66.6, 65, and 65 %, respectively. The rest of the studies described somewhat lower percentages of initial negative behavior in these patients (Loo et al 2008;Harada and Nishino 2005).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the pre-test, 73.7 % of children and 67.6 % of adults showed a reluctant behavior (Frankl values 1 and 2); a similar percentage to that observed initially by Lowe and Jędrychowski (1987), Klein and Nowak (1999), Chaushu and Becker (2000), Marshall et al (2008), and Subramaniam and Gupta (2011) with 70, 72, 66.6, 65, and 65 %, respectively. The rest of the studies described somewhat lower percentages of initial negative behavior in these patients (Loo et al 2008;Harada and Nishino 2005).…”
Section: Discussionsupporting
confidence: 80%
“…This scale has been used to evaluate behavior of patients with ASD on their first visit to the dentist (Klein and Nowak 1999;Loo et al 2008 (Marshall et al 2008) and, finally, to select patients for treatment under general anesthesia or sedation (Chaushu and Becker 2000;De Nova-García et al 2007).…”
Section: Compliancementioning
confidence: 99%
“…Consistent with this, a study focused on assessing the eating habits and intake of nutrients in children with ASDs, by Schmitt et al (2008), found that 70% of children with ASDs selected what they ate according to texture compared to 11% of children without ASD. Whiteley et al (2000) indicated an even higher rate (83%) of parents reporting that their children ate a restricted repertoire of foods, while Klein and Nowak (1999) found that just over half (53%) of their patients were unwilling to try new foods. In general, Bandini et al (2010) indicated that children with ASDs rejected food more often that DT children (41.7% of foods offered compared to 18.9%).…”
Section: Introductionmentioning
confidence: 99%
“…Behaviour management, including communication, and pharmacological and immobilization techniques, is necessary in order to successfully treat patients with AS [8]. According to the Frankl scale, our case was classified as "definitely negative".…”
Section: IIImentioning
confidence: 96%